INFLUENCE OF BORDER INFRASTRUCTURE ON TRADE AND ECONOMIC GROWTH IN BORDER AREAS - Melyana R Pugu; Muhammad Syafri; Nahot Tua Parlindungan Sihaloho; Mohd Syahrin (Adisam Publisher, 2024)
Border infrastructure has an impact on trade and economic growth for communities living on the border. This method of investigation uses the study of literature by searching for references that fit the context of the research. The results of the research show that the improvement of the infrastructure in the border area has a significant positive impact on the volume of trade, with reduced logistics costs and improved efficiency of the flow of goods and services. Better infrastructure is strongly correlated with higher levels of foreign investment and closer regional economic integration. Further analysis shows that increased access to education, health care, and public services, catalysed by infrastructure investment, significantly contributes to economic and social development in the border areas. The research also found that strong border infrastructure increases economic resilience to external disturbances and drives long-term growth through economic diversification and innovation.